Pendekatan Hukum Pemerintah Indonesia terhadap Pemulihan Aset dari Negara Non- Aeoi: The Indonesian Government's Legal Approach to Asset Recovery from Non-AEEOI Countries - Rilo Pambudi, Rustu; Tanzil Multazam, Muhammad (Faculty of Law Hang Tuah University, 2025)
This research aims to analyze the impact of the legal vacuum in international tax treaties on Automatic Exchange of Information (AEoI) on tax avoidance practices in Indonesia, as well as to find ways that the state driven by the government can withdraw assets from individuals and entities hidden in tax heaven countries whose tax treaties do not contain global information exchange standards set by the OECD, the research method used is a normative juridical approach with qualitative analysis. Primary data was obtained through document studies of national and international regulations, while secondary data was obtained from literature, journals, and reports of international institutions such as the OECD and the Global Forum, the results showed that the legal vacuum at the level of technical implementation of AEoI in Indonesia led to the low effectiveness of cross-border data exchange. This opens a gap for taxpayers to move assets to jurisdictions that do not have active AEoI agreements, which ultimately reduces the potential for state revenue from foreign taxes and the inability of the state to retrieve and or confiscate assets from individuals and entities obtained by harming the state and society such as organ trafficking, tax evasion, transfer pricing to corruption, These findings confirm the need for harmonization of domestic regulations with international standards, This recommendation is important to strengthen the integrity of the national tax system and prevent cross-border tax evasion and concealment practices. These recommendations are important to strengthen the integrity of the national tax system and prevent the practice of tax evasion and concealment of cross- border assets.